Ex vitro micrografting aiming the CABMV virus elimination in passion fruit plant - Ribeiro, Leonardo Monteiro; Peixoto, José Ricardo; Andrade, Solange Rocha Monteiro de; Fonseca, Rúbia Santos; Vieira, Lorena Melo; Pereira, Wilson Vicente Souza (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the effect of different culture media, used over grafting spot, in ex vitro micrografting, in order to eliminate the Cowpea aphid-borne mosaic virus (CABMV) in sour passion fruit plants (Passiflora edulis Sims f. flavicarpa Deg.). Cauline apexes, originated from infected plants, were micrografted in seedlings obtained by the germination of seeds in commercial sterilized substrate. Experiments were conducted with the micrografting performed on the hypocotyl and epicotyl using five culture media, which differed on their concentration of phytoregulators applied on the grafting spot. The average rate of micrografting showing expanded leaf was 27.22 and 32.22%, when micrografting was performed on hypocotyl and epicotyl, respectively. In the micrografting performed on the hypocotyl, there was no effect of the culture media applied. In the micrografting performed on epicotyl, the MS medium supplemented with 0.1 mg L-1 3-indolbutiric acid (IBA) and 1 mg L-1 6-benzylaminopurine (BAP) resulted in 53.3% of micrografting showing expanded leaf, a number superior to the other treatments, and in a larger development of shoots. The indexing performed by the indirect ELISA test, within 80 to 100 days after micrografting, showed that 93% of the plants tested presented no detectable virus.